The use of selected information skills in the ABS-CBN distance learning center - Marcoleta, Libni M. (2000)
This study aimed at determining the extent to which a selected list of technology-based information skills is applied in distance education, with the view of finding out how these skills helped the students cope with the nature and requisites of distance learning process and eventually, to recommend modest inputs in improving this type of academic program.